International cooperation. Outreach projects - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
A cooperative project between Central American countries and CIAT to increase bean production in the region was initiated in 1980. The following activities were stimulated: (1) Interinstitutional technology transfer by distribution through CIAT yield and adaptation nurseries and national programs; black-seeded var. ICTA-Jutiapan, ICTA-Quetzal, and Talamanca, and red-seeded var. Acacias-4 and Revolucion 79 had a good performance through-out the region. (2) Seed production, by strengthening seed programs in Guatemala, Honduras, Costa Rica, and Nicaragua. National programs in El Salvador, Cuba, Honduras, and Nicaragua received seed from the Bean Program and the CIAT seed unit. (3) Training, 25 bean researchers in the region received postgraduate training at CIAT and technical and organizational assistance was provided for a short course on bean production held in Cuba. (4) Screening for BGMV, which resulted in several promising BGMV-tolerant materials. The project in Peru completed its 2nd yr of operation. Regional trials are carried out with materials from the International Bean Yield and Adaptation Nursery (IBYAN) at CIAT and with local materials. Two appendixes are included: (1) detailed description of Phaseolus vulgaris growth habits and (2) list of CIAT accessions of Phaseolus referred to in this report, including CIAT no. of accession, identification, local register, and source. (CIAT)